Development of a Core Outcome Set in the Clinical Trials of Traditional Chinese Medicine for Stroke: A Study Protocol - Zhang, Ting; Li, Xuechao; Zhao, Liang; Zhang, Jiaoyan; Tian, Jinhui; Zhang, Junhua (Frontiers in Medicine, 2022)
Introduction: Stroke, an acute cerebrovascular disease, is mainly caused by the sudden rupture or occlusion of blood vessels, and is subdivided into ischemic stroke and hemorrhagic stroke. Stroke has become the second leading cause of death worldwide. In Chinese clinical practice, traditional Chinese medicine (TCM)/Integrative Medicine have been widely used for the treatment of stroke. Numerous randomized controlled trials (RCTs) of TCM/integrative medicine for stroke have conducted to improve the efficacy and safety outcomes on stroke. However, their conclusions should be treated with caution because of the methodological quality defects in clinical research. Pervasive inconsistencies are present in the outcomes collected and reported across these studies, which may lead to the pooling of discrepant data and preclude meta-analysis. The issue could be addressed by developing a core outcome set (COS). Aims: The aim of this study is to develop a COS in the clinical trials of TCM/Integrative Medicine in the treatment of stroke. Method and Analysis: A Steering group will be set up to organize and guide the development of this COS. The study contains three phases: (I) we will develop an initial outcome list covering all relevant outcomes, via two steps: (i) systematic reviews of outcomes for clinical trials of TCM/ Integrative Medicine for stroke; (ii) semi-structured interviews with stroke patients; (II) we will conduct three round Delphi survey with different stakeholder groups to prioritize important outcomes; (III) we will integrate outcomes into a core outcome set by a consensus meeting. Ethics and Dissemination: This study has been granted by the Ethics Committee of Tianjin University of Traditional Chinese Medicine (TJUTCM-EC20210003). When the COS is completed, we will publish it in an appropriate journal to promote further widespread use. Registration: This study has been registered at Core Outcome Measures in Effectiveness Trials initiative, COMET database (registration #1678).